EFFECTS OF MOTOR IMAGERY ON BALANCE, DEPRESSION AND STRESS IN ELDERLY: RANDOMIZED CONTROLLED TRIAL - Pakulanon, Sasima; Petviset, Haruthai; Yingyongsaksri, Supannikar (Academic Journal of Thailand National Sports University, 2024)
This research aimed to investigate the effects of motor imagery on balance, depression, and perceived stress in the elderly. Thirty-seven healthy male and female participants aged 60 to 75 years old were randomly divided into two groups. The training group (n = 18, aged 68.06 ± 3.11 years old) underwent motor imagery training for 4 weeks, while the control group (n = 19, aged 66.53 ± 3.56 years old) did not receive any training. Before and after 4 weeks of training, all participants were assessed for balance using the Timed Up and Go Test, depression using TDGS-15, and stress using the Perceived Stress Scale. A two-way repeated-measure ANOVA was used to test the group and time interaction effect, and the Bonferroni method was employed for multiple comparisons. The level of significance was set at 0.05, indicating a significant difference. The results showed a significant improvement in balance in the training group (p < 0.05). Additionally, a significant decrease in depression score was observed in the training group (p < 0.05). No significant interaction effects of group and time were found in the stress score. While the stress score of the training group showed a trend toward decrease after 4 weeks of training, no significant difference was found. In conclusion, motor imagery can be utilized to enhance balance performance and alleviate depression in the elderly.